Ultraviolet protection performance of cotton fabric modified by ionic liquid iron coordination complex. Issue 8 (May 2017) - Cheng, Dehong; Yu, Zhi-Cai; Lu, Sheng; Gong, Shengchen; Li, Jia; Wang, Boxiang; Lu, Yanhua
In order to endow cotton fabric with the full wave band (290–410 nm) ultraviolet (UV) protection property, ionic liquid iron coordination complex (ILICC) was applied to modify cotton fabric. ILICC was prepared by in situ reaction on the surface of the cotton fiber directly. The Fourier transform infrared spectra, thermogravimetric and differential scanning calorimetry curves indicated that the strong interaction between ILICC and cellulose macromolecules of cotton fiber occurred through the O-Fe bond. Scanning electron microscopy images and particle size analysis indicated that the surface of the modified cotton fiber was covered by the agminate ILICC particles with diameters of 700–1600 nm. Investigation on the UV protection performances indicated that the UV transmittances ( T %) of the modified cotton fabric were less than 1.3% for the full wave band (UVA and UVB) UV. The washing durability results showed that the UV protection factor values were more than 95 when the modified cotton fabric was washed with 30 st washing cycles. The reason for the excellent UV protection performance of the modified cotton fabric was absorption and shielding of ILICC particles to UV light.